2021
DOI: 10.3389/fimmu.2021.530488
|View full text |Cite
|
Sign up to set email alerts
|

Elevated microRNA-21 Is a Brake of Inflammation Involved in the Development of Nasal Polyps

Abstract: BackgroundCRSwNP is an inflammatory disease but the mechanism is not yet fully understood. MiR-21, a member of miRNAs, has been reported to play roles in mediating inflammation. However, the expression of miR-21 and its role in patients with CRSwNP remain elusive.MethodsTurbinates from control subjects, uncinate processes from CRSsNP, polyp tissues from CRSwNP, and nasal epithelial cells brushed from nasal mucosa were collected. The expression of miR-21 and cytokines in nasal tissues and epithelial cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“… 10 Liu et al found that upregulated miR-21 can inhibit activation of NF-κB P65 and increase IL-10 expression through targeting to PDCD4 in nasal epithelial cells, which could further limit the expression of pro-inflammatory cytokines in CRSwNP. 11 Although many studies have indicated differential expressions of circRNAs and miRNAs between patients with CRSwNP and other patients or controls, the specific regulatory mechanisms through regulation of circRNA/miRNA/mRNA networks contributing to CRSwNP remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Liu et al found that upregulated miR-21 can inhibit activation of NF-κB P65 and increase IL-10 expression through targeting to PDCD4 in nasal epithelial cells, which could further limit the expression of pro-inflammatory cytokines in CRSwNP. 11 Although many studies have indicated differential expressions of circRNAs and miRNAs between patients with CRSwNP and other patients or controls, the specific regulatory mechanisms through regulation of circRNA/miRNA/mRNA networks contributing to CRSwNP remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In nasal epithelial cells, TGF-β1 is claimed to promote EMT via the upregulation of α-smooth muscle actin, leading to polyp formation. [ 32 ] Furthermore, Fan et al [ 16 ] revealed that miR-203a-3p is underexpressed and regulates TGF-β1-induced EMT in asthma patients. By targeting SIX1, miR-203a-3p, regulates the Smad3 pathway, thus inhibiting TGF-β1 and stopping the induction of EMT in bronchial epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, Lund‐Kennedy and Lund‐MacKay scores are commonly used to determine the disease severity of CRS patients (Bezerra et al, 2021). Because CRS comprises a wide array of mechanisms for pathophysiology, there are few markers labeling the generation and predicting the progress of CRS, which brings great difficulties to clinical diagnosis, treatment, and prognosis (Liu et al, 2021). Based on clinical data collected in this study, we analyzed Lund‐Kennedy and Lund‐MacKay scores of all CRS patients.…”
Section: Discussionmentioning
confidence: 99%